Tinjauan Tentang Larangan Praktik Monopoli dan Persaingan Usaha Tidak Sehat Terhadap Dominasi Penjualan Rokok Merek Sampoerna di Wilayah Kecamatan Kampar Timur - Wahyuni, Maida; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
On the basis of article 4 paragraph (1) of Act No. 5 Of 1999 Year Antitrust explained thatbusinessmen are prohibited from making agreements with other businessmen to jointly conduct a mastery ofthe production and marketing of the goods or and or service can result in the occurrence of monopolisticpractices and/or unhealthy business competition, it is in accordance with the activities of the banned Partyconducted the Sampoerna represented by the agent. Party Sampoerna has conducted cooperation with thestore owner who is Kampar Sub-district of Eastern region, that businessmen who had made that agreementwill not receive promotional materials from other businessmen or smoking other stores only focus on thepromotional materials of the Sampoerna only. Activities performed by the Treaty the sampoerna partycontrary to the contents of article 19 of the Act number 5 Year 1999 regarding mastery of the marketexplains the businessmen are prohibited from performing one or more activities, either alone or otherbusinessmen jointly led to competition and antitrust practice efforts is not healthy. The purpose of writingthis thesis, namely; First, figure out the implementation of the rights and obligations held the trademonopoly and competition practices pose a business isn't healthy, secondly, knowing the legal efforts resultfrom the cooperation agreement.This type of research can be classified in types of sociological research, because in this study theauthors direct research on the location or place a complete thorough in order to give a complete and clearpicture of the problems researched.From the results of the research there are two staples that can be summed up: first, theimplementation of the rights and obligations of trade raises monopoly and competition of unhealthybusinesses and the implementation of Act No. 5 of year 1999 has not yet been fully realised due to lack ofunderstanding of the people against the monopolistic practices Act. Second, efforts are being made in thepelaksaan Agreement committed the parties Sampoerna which resulted in competition and antitrustpractices effort was to provide socialization to society who do not understand about violations in agreementto the detriment of other businessmen as indicated in Act No. 5 of year 1999, later for businessmen who dopractice prohibited monopolies should be given strict sanctions by the relevant agencies of the Government,through the the authorized institution such as the Commission's competition Watchdog's efforts to superviseand investigate the behavior of businesses that practise a monopoly.